The role of high-field magnetic resonance imaging in parkinsonian disorders: Pushing the boundaries forward - Lehericy, Stéphane; Vaillancourt, David E; Seppi, Klaus; Monchi, Oury; Rektorova, Irena; Antonini, Angelo; McKeown, Martin J; Masellis, Mario; Berg, Daniela; Rowe, James B; Lewis, Simon J G; Williams-Gray, Caroline H; et al. (Movement disorders, 2017)
Historically, magnetic resonance imaging (MRI) has contributed little to the study of Parkinson's disease (PD), but modern MRI approaches have unveiled several complementary markers that are useful for research and clinical applications. Iron- and neuromelanin-sensitive MRI detect qualitative changes in the substantia nigra. Quantitative MRI markers can be derived from diffusion weighted and iron-sensitive imaging or volumetry. Functional brain alterations at rest or during task performance have been captured with functional and arterial spin labeling perfusion MRI. These markers are useful for the diagnosis of PD and atypical parkinsonism, to track disease progression from the premotor stages of these diseases and to better understand the neurobiological basis of clinical deficits. A current research goal using MRI is to generate time-dependent models of the evolution of PD biomarkers that can help understand neurodegeneration and provide reliable markers for therapeutic trials. This article reviews recent advances in MRI biomarker research at high-field (3T) and ultra high field-imaging (7T) in PD and atypical parkinsonism. © 2017 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.
Keywords: diffusion MRI; parkinsonské poruchy; atypical parkinsonism; MRI; Parkinson's disease; resting state fMRI; Humans; zobrazování trojrozměrné; iron; fMRI; 7T; Parkinsonian Disorders; lidé; magnetická rezonanční tomografie; Imaging, Three-Dimensional; Magnetic Resonance Imaging; neuromelanin